COMBINATION OF PLANTING METHODS AND MULTIPLE NPK FERTILIZER ON PLANT GROWTH AND PRODUCTION SWEET CORN (Zea mays saccharata Sturt) - Erni Hawayant; Berliana Palmasari; Nopriyanto Nopriyanto; Nico Syahputra Sebayang (Biotik, 2021)
This study aims to obtain differences in the response of growth and yield of Sweet Corn (Zea mays saccarhata Sturt) using a single row planting system and a two row planting system. This research was conducted in Sukajadi Village, Banyuasin Regency, South Sumatra Province. Research time in January. This study used a split plot design with 8 treatment combinations which were repeated 4 times. The treatment factors in question are as follows: Main Plot : Single Row Planting System (S1), Two Row Planting System (S2), P0: No treatment , P1: NPK : 60g (plot) P2: NPK : 120g (plot) P3 : NPK : 180g (plot). The variables observed in this study were plant height/plant (cm), length of seed cob/plant (cm), cob weight/plant (gr), production of plots/plot (kg). Based on the results of the study, it was shown that the treatment with a two-row planting system (DB) and application of 300kg/ha compound NPK fertilizer gave the best effect on sweet corn production of 12.96 kg/plot or equivalent to 17.28 tons/ha.